The Influence Of Occupational Safety On The Performance Of BPBD Aceh Tamiang Employees - Syardiansah, Syardiansah; Maysari, Shinta; FW Pospos, Ade Fadilah (KINERJA, 2024)
This study aims to find out how the influence of work safety on the performance of employees of the Regional Disaster Management Agency (BPBD) of Aceh Tamiang Regency. The population in this study were all employees at BPBD Aceh Tamiang District. The sample in this study amounted to 32 respondents who were taken using a saturated sampling technique. The research method used is a quantitative method, by obtaining data through interviews, distributing questionnaires and studying the literature. This study gives the result that the linear regression formula in the study is Y = 0.769 + 0.950X1. From this it can be interpreted that work safety has a positive influence on the performance of BPBD Aceh Tamiang Regency employees. Simultaneously and partially, work safety has a significant influence on the performance of BPBD Aceh Tamiang employees where the t sig value is 0.001 <0.05. The coefficient of determination of the work safety variable is 0.548, meaning that the work safety variable is able to influence the performance variable by 54.8%, while the remaining 45.2% is influenced by other variables not examined in this study.